2019
DOI: 10.1002/cmdc.201900426
|View full text |Cite
|
Sign up to set email alerts
|

Design and Biological Evaluation of Manganese‐ and Ruthenium‐Based Hybrid CO‐RMs (HYCOs)

Abstract: Interest in the therapeutic effects of carbon monoxide (CO), a product of heme degradation catalyzed by the enzyme heme oxygenase‐1 (HO‐1), has led to the development of CO‐releasing molecules (CO‐RMs) for the controlled delivery of this gas in vivo. We recently proposed conjugating a cobalt‐based CO‐RM with various activators of nuclear factor erythroid 2‐related factor 2 (Nrf2), the transcription factor that regulates HO‐1 expression, in order to exploit the beneficial effects of exogenous and endogenous CO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…63 Another novel class of molecules with potent anti-inflammatory action in models of skin wound, psoriasis, and multiple sclerosis are HYCOs, hybrid compounds consisting of a CO-RM conjugated to a Nrf2/HO-1 activator. [64][65][66][67][68] Recent studies have been demonstrated that is not readily discriminated whether an observed effect of a CO-RM is caused by the release of carbon monoxide gas, the CO-RM itself, or any of its intermediate or final breakdown products. 69 Thus, a radical intermediate formed during carbon monoxide release from ruthenium (Ru)based CORM-2 is likely responsible for the CORM-2-mediated inhibition of diverse snake and lizard venoms.…”
Section: T a B L E 1 The Antinociceptive Effects Of Carbon Monoxide Amentioning
confidence: 99%
See 1 more Smart Citation
“…63 Another novel class of molecules with potent anti-inflammatory action in models of skin wound, psoriasis, and multiple sclerosis are HYCOs, hybrid compounds consisting of a CO-RM conjugated to a Nrf2/HO-1 activator. [64][65][66][67][68] Recent studies have been demonstrated that is not readily discriminated whether an observed effect of a CO-RM is caused by the release of carbon monoxide gas, the CO-RM itself, or any of its intermediate or final breakdown products. 69 Thus, a radical intermediate formed during carbon monoxide release from ruthenium (Ru)based CORM-2 is likely responsible for the CORM-2-mediated inhibition of diverse snake and lizard venoms.…”
Section: T a B L E 1 The Antinociceptive Effects Of Carbon Monoxide Amentioning
confidence: 99%
“…Other CO‐RMs that release carbon monoxide under irradiation (PhotoCORMs), including unsaturated cyclic diketones, xanthene carboxylic acids, meso‐carboxy BODIPYs, and hydroxyflavone, have also been demonstrated to produce potent anti‐inflammatory effects 63 . Another novel class of molecules with potent anti‐inflammatory action in models of skin wound, psoriasis, and multiple sclerosis are HYCOs, hybrid compounds consisting of a CO‐RM conjugated to a Nrf2/HO‐1 activator 64–68 …”
Section: Ho‐1 and Carbon Monoxide In Painmentioning
confidence: 99%
“…Complexes containing manganese ions have shown significant ability to be used as drugs [ 4 , 5 , 6 ]. Furthermore, the Mn(II) ion in a metal–ligand framework has found application as an inhibitor of MtDXR ( Mycobacterium tuberculosis ) [ 7 , 8 , 9 ]. Comprehensive studies have been conducted on Fe-based compounds, especially ferrocifen.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been efforts in encapsulating metal-based CO-RMs for reduced metal exposure [31][32][33]. The Motterlini lab has recently reported hybrid CO-RMs through conjugation with an activator of HO-1 with the aim of creating synergy with endogenously produced CO [34,35]. These metalimmobilized carbonyls have played a very significant role in understanding CO physiology and in demonstrating pharmacological efficacy in various animal models.…”
Section: Introductionmentioning
confidence: 99%